Enhanced precipitate growth at reduced temperatures during chemical ordering in deformed red gold alloys. (September 2019) - Garcia-Gonzalez, Marina; Van Petegem, Steven; Baluc, Nadine; Hocine, Samy; Dupraz, Maxime; Lalire, Fanny; Van Swygenhoven, Helena
Abstract: Manufacturing of red gold components relies widely on controlling the formation of ordered precipitates during thermo-mechanical processing. The ordered phase hardens the material, makes it less workable and introduces residual stresses. We show that an industrial wire straightening process on chemically disordered wires enhances the formation of ordered precipitates in the near surface region during natural ageing. To address the role of plastic deformation during artificial ageing, in situ X-ray experiments are carried out on deformed and undeformed samples. It is shown that pre-deformation decreases the onset temperature for ordering and enhances precipitation growth at the early stages of the transformation. Graphical abstract: Unlabelled Image